Clinical Profile of Indian Patients Undergoing Percutaneous or Surgical Coronary Revascularization in the Modern Era - Manish Bansal; Ravi R Kasliwal; Praveen Chandra; Rajneesh Kapoor; Nagendra Chouhan; Anil Bhan; Naresh Trehan (Journal of Clinical and Preventive Cardiology)
Background: Coronary artery disease (CAD) is among the leading causes of death worldwide, and its prevalence is rising rapidly in India. Revascularization is an important mode of treatment for CAD. Unfortunately, only limited information is available regarding the clinical characteristics of the patients currently undergoing coronary revascularization in India. Methods: This was a retrospective study conducted at a premier, tertiary care center in North India. A total of 2847 consecutive subjects (mean age 61.3 ± 10.3 years, 2374 [83.4%] men) undergoing coronary revascularization were included. Results: Overall, percutaneous transluminal coronary angioplasty (PTCA) was a more common mode of coronary revascularization than coronary artery bypass graft surgery (CABG) (58.1% vs. 41.9% of patients). Although there was a higher usage of CABG among males, older patients, patients with diabetes mellitus (DM), and those presenting with stable CAD, PTCA was still the preferred mode of revascularization. Only in patients with triple-vessel CAD or left main CAD, CABG was performed more commonly than PTCA (64.7% vs. 35.3% for triple-vessel disease and 81.4% vs. 18.6% for left main disease). When compared with a previous group of 1000 patients who had undergone CABG in the year 2004, the patients in the current cohort were older, had less hypertension but a higher prevalence of DM, and had lower levels of total cholesterol and low-density lipoprotein cholesterol. Conclusion: Our study describes the clinical profile of patients currently undergoing coronary revascularization in North India. The study showed that PTCA was the preferred mode of coronary revascularization in most patients, except in those with triple-vessel CAD or left main CAD. Compared with the PTCA patients, those undergoing CABG had a consistently higher prevalence of diabetes, across all clinical subgroups. Further prospective studies are required to determine the long-term clinical implications of these findings.